Biomedical Application of Magnetic Nanoparticles: A Review - Paudel, Eak Raj (BMC Journal of Scientific Research, 2022)
Medical treatment technologies in healthcare industries are modernized by using nanoparticles. The effect of nanoparticles and their interaction on human cells show many significant results. In this paper, I have studied the experimental and theoretical background of some biomedical applications of nanoparticles. It is found that gold (Au), silver (Ag), iron (Fe), silica (SiO2), and some polymeric nanoparticles are extensively used in the treatment of various deadly diseases. The nanoparticles of gold, silver, zinc oxide, silica, and cerium oxide are studied mostly to investigate the suitable distribution methodology for medical diagnosis and treatment.